Quantum weirdness - Mullin, William J. (Oxford University Press, 2017)
Quantum mechanics allows accurate predictions of nature, yet it also uncovers surprises like teleportation and multiple universes. It involves complicated mathematics, yet most general reader texts avoid mathematics. This book uses on high-school level mathematics to provide a deeper understanding of quantum mechanics.